On the possibility of controlling the temperature of gases and liquids in a transportation system by local cooling or heating with account salt deposition - Evgeny L. Pankratov (International Journal of Research in Industrial Engineering)
In several technical applications, it is necessary to conduct a heat sink. For example, a liquid or gas is passed through the reactor zone and removes the heat released from it as a result of the nuclear fission reaction. It also attracts an interest in removing overheating during the operation of power lasers. On the other hand, in some cases, it has attracted an interest in deliberate heating during the operation of devices. An example of such heating is heating of the reaction zone in reactors for gas phase epitaxy. In both cases, the heat sink is a passive heat exchanger. At the same time, in some applications, it is necessary to stabilize the temperature of a liquid or gaseous heat carrier. In this paper, we consider a cylindrical transportation system (as a pipeline) of liquid or gas with a circular section with a known dimension, which is contained within a porous metal. This section has a stable temperature. The main aim of this paper is to analyse the distribution of gas and liquid temperature in the considered pipeline under the influence of heating and cooling of local sections of the pipeline. The accompanying aims of this paper are a formulation of a model to describe heat transport in the pipeline with a section that has a stable temperature and the development of an analytical approach for analyzing the obtained model. The model is based on an analytical solution of partial differential equations with nonlinearity and variation of their coefficients in space and time. The model became more adequate in comparison with recently considered models with better coincidence of experimental results with calculated ones.